1992
DOI: 10.1007/bf00182706
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in paragliding

Abstract: In a retrospective study, 376 paragliding accidents have been analysed. Leg injuries were most common, but a large number of spinal injuries also occurred. The causes were either misjudgement by the pilot or the influence of weather and terrain. Improvements in the instructor's knowledge and the pilot's training could have prevented most of the accidents. Analysis of the mechanisms of the crashes and the pattern of trauma help to produce an efficient approach to diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 9 publications
2
13
1
6
Order By: Relevance
“…8,9 In contrast to these and to epidemiological data on SCI in Norway, paragliding injuries are more homogeneous, as serious neck and head trauma is rare, indicating that the spinal cord and spine are at high risk due to vertical highenergy force evoked toward the spine due to the paraglider's fixed body position. 1,3,10,11 Demographically, the paragliders with SCIs were similar to those in the general population of Norway, with clear male predominance. 10,11 Interestingly, most of the paragliders in our study were experienced, and the causes of accidents were unexpected circumstances and misjudgments in the landing process.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…8,9 In contrast to these and to epidemiological data on SCI in Norway, paragliding injuries are more homogeneous, as serious neck and head trauma is rare, indicating that the spinal cord and spine are at high risk due to vertical highenergy force evoked toward the spine due to the paraglider's fixed body position. 1,3,10,11 Demographically, the paragliders with SCIs were similar to those in the general population of Norway, with clear male predominance. 10,11 Interestingly, most of the paragliders in our study were experienced, and the causes of accidents were unexpected circumstances and misjudgments in the landing process.…”
Section: Discussionmentioning
confidence: 77%
“…1,3,7 Landing at high speed on straight feet or crashing on the buttocks puts the thoracolumbal junction of the spine at risk for fractures caused by high energy. Similar injuries have been reported among skydivers and among snowboarders 8,9 indicating that this type of extreme sport increases the risk of spine injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports suggested that by refi nement of pilot education, deliberate use of protective equipment, and better understanding of inherent aerodynamics of paragliding, the injury rates can be lowered. [2,6,17,18] In our study, only patients admitted to hospitals were reported as having injuries. Obtaining results from only one specifi c touristic region is one of limitations of this study.…”
Section: Discussionmentioning
confidence: 85%